Sodium lignosulfonate as sacrificial agent and effectiveness in reducing CTAB cationic adsorption onto kaolinite - Aik Shye Chong (Elsevier, 2021)
Sodium lignosulfonate (SLS) as sacrificial agent (SA) was investigated on the effectiveness in reducing Cetyl Trimethyl Ammonium (CTAB) cationic surfactant adsorption. X-Ray diffractometer (XRD), X-Ray fluorescent (XRF), Scanning electron microscopy (SEM), electron dispersive X-Ray (EDX) and Brunauer-Emmet-Teller (BET) were used to characterize the mineralogy, elemental composition and surface area of kaolinite. Fourier transform infrared-attenuated total reflectance (FTIR-ATR) was used to characterized kaolinite and SLS. The adsorption was done by depletion method using Ultraviolet–visible spectroscopy (UV–Vis). Effectiveness as sacrificial agent in mixture and pre-treatment were studied. The underlying mechanism that responsible for the effectiveness of SA were interpreted and examined. Positive outcome shows that SLS as SA manages to reduce CTAB adsorption. The SLS as SA successfully in reducing CTAB adsorption by using pre-treatment method. Effective underlying mechanism involved is SLS as SA adsorbed readily with the cation bridging assistance from the divalent salt and reversed the surface charge by creating a second layer. As high as 50% CTAB reduction had been seen in the experimental work. This study shows that SLS as SA effectively reducing the CTAB adsorption in pre-treatment.